The Effect of Ultrasonic Wave Exposure on The Chlorophyll-a, b And Carotene Content of Nannochloropsis sp. - Hadi Endrawati; Muhammad Zainuri; Widianingsih Widianingsih; Retno Hartati; Robertus Triaji Mahendrajaya; Sri Redjeki; Ita Riniatsih; Ria Azizah (Jurnal Kelautan Tropis, 2018)
Determination of chlorophyll-a, b and carotene content in microalgae is strongly dependent on the destruction of its cell wall during extraction process.  Harvesting of microalgae is important  because it will influence the nutrition content. The objective of present work is to optimize harvesting of Nannochloropsis sp by application of ultrasonic wave with frequency of 40 KHz under different exposure time.  There were 3 treatments, i.e. exposure time of 5, 10 and 15 minutes.  The chlorophyll-a, b, and carotene content were measured to gauge the effect of treatments. The result revealed that the cell wall of Nannochloropsis sp which made from carbohydrate were successfully broken by ultrasonic source equipment. It showed that the exposure time of  5, 10 and 15 minutes affected cell wall’s breaking percentage of Nannochloropsis sp cell by 10,35;  32,15; and 72,09 %, respectively. The longer exposure time of ultrasonic wave, the higher content of  chlorophyll-a, b, and carotene.